Development of Active Organic and Polymeric Materials for Batteries and Solar Cells: Introduction to Essential Characterization Techniques. Issue 24 (1st October 2015) - Friebe, Christian; Schubert, Ulrich S.
Abstract : Establishing renewable energy sources is currently one of the major scientific topics. Two aspects are most crucial: energy conversion and energy storage. Thus, the development of efficient solar‐cell devices and high‐capacity, high‐current rechargeable battery systems turns out to be of great importance. In particular, the design of active materials and their characterization using electrochemical and spectroscopic means represent essential elements in the development process. Here, a concise overview of both methods and key properties with regard to the characterization of organic and polymeric active materials with a focus on energy conversion/storage is provided. Benefits and limitations of complementary techniques are presented to enable a consistent and comprehensive characterization procedure. Abstract : With regard to a changing worldwide energy distribution policy towards renewable systems, more and more research is focused on solar‐based energy conversion and related energy‐storage technologies. Basic techniques for the characterization and development of solar cells and battery devices that are based on organic and polymeric active materials are discussed.